Obstetrical Complications in Women with Endometriosis: A Cohort Study in Japan - Harada, Takashi; Taniguchi, Fuminori; Onishi, Kazunari; Kurozawa, Youichi; Hayashi, Kunihiko; Harada, Tasuku; Japan Environment & Children’s Study Group (PLOS ONE, 2016)
Background Endometriosis, which occurs in approximately 10% of women of reproductive age, is defined as the presence of endometrial tissue outside the uterus. Women with endometriosis are more likely to have difficulty conceiving and tend to receive infertility treatment, including assisted reproductive technology (ART) therapy. There has not yet been a prospective cohort study examining the effects of endometriosis on pregnancy outcome in pregnant Japanese women. Methodology This was a prospective cohort study of the incidence of obstetrical complications in women with endometriosis using data of the Japan Environment & Children’s Study (JECS). Included in this study were 9,186 pregnant women in the JECS with or without a history of endometriosis who gave birth or stillbirth or whose pregnancy was terminated with abortion between February and December 2011. Main Outcome Measures The effects of endometriosis on pregnancy outcome. Results Of the 9,186 pregnant women in the JECS, 4,119 (44.8%) had obstetrical complications; 330 participants reported a diagnosis of endometriosis before pregnancy, and these women were at higher risk for complications of pregnancy than those without a history of endometriosis (odds ratio (OR) = 1.50; 95% confidence interval (CI) 1.20 to 1.87). Logistic regression analyses showed that the adjusted OR for obstetrical complications of pregnant women who conceived naturally and had a history of endometriosis was 1.45 (CI 1.11 to 1.90). Among pregnant women with endometriosis, the ORs of preterm premature rupture of the membranes (PROM) and placenta previa were significantly higher compared with women never diagnosed with endometriosis who conceived naturally or conceived after infertility treatment, except for ART therapy (OR 2.14, CI 1.03–4.45 and OR 3.37, CI 1.32–8.65). Conclusions This study showed that endometriosis significantly increased the incidence of preterm PROM and placenta previa after adjusting for confounding of the data by ART therapy.